Wojna o wodę – wyzwanie dla bliskowschodnich armii w XX i XXI w. - Pogońska-Pol, Magdalena (Armia kontra natura, 2020)
Due to geographical conditions, climate and political instability, the Middle East is mentioned as an area of future water conflict. In the 20th and 21st centuries there were numerous disputes over this raw material. Conflicts have both internal and external dimensions. The main dispute was between Israel and the Arabs and indirectly led to the June 1967 war. The Arab states also used the army as a deterrent in the race for water. The competition takes place on the line Iraq, Syria, Turkey. Water has also been used as a weapon in the Middle East. ISIS fought for dams to use them strategically and tactically.